INVESTIGATING ONLINE SPEAKING CLASS FOR SEVENTH GRADERS OF UPT SMPN 25 GRESIK DURING COVID-19 PANDEMIC - HAPPY KUSUMA WARDANI; NURI ZAKIYAH (Program Studi Pendidikan Bahasa Inggris Fakultas Keguruan dan Ilmu Pendidikan, 2021)
The COVID-19 pandemic has an impact on all sectors, especially in the education field. It caused many countries to close down the schools of all stages to curb the spread of the virus. The teachers and students have to abandon their face-to-face classrooms and adapt to the implementation of online learning. Thus, the teachers were challenged to carry out online learning during this pandemic. Within this context, this research aims to investigate the online learning of Speaking Skills for seventh graders of UPT SMPN 25 Gresik. In this qualitative research, an EFL teacher of UPT SMPN 25 Gresik became the subject of the observation. The instruments used in this research were observation sheets and field notes. The result of the observation showed that the teacher in the seventh grade of UPT SMPN 25 GRESIK has carried out the online learning of speaking well through a series of activities that could stimulate students' attention. The research outcome is expected to encourage other EFL teachers to be creative in carrying out online learning in this transitional period. Moreover, the research is expected to pave the way for developing solutions and anticipating the problems that may come up in online learning at secondary schools, especially in teaching online learning for Speaking skills.